ANALISIS FAKTOR STATUS GIZI BURUK PADA BALITA DI PUSKESMAS CEBONGAN KOTA SALATIGA - Helmy Apreliasari; Risnawati . (STIKES DUTAGAMA KLATEN, 2020)
Good nutrition is a key condition of health and has an impact on the quality of human resources. According to the World Health Organization (WHO) malnutrition is determined based on anthropometric indicators according to weight to height length (BW/BH) with z-score of W/H of ≤ 3 SD and the presence or absence of edema. This study aims to determine the factors associated with malnutrition status among under-five children. This was a quantitative analytic descriptive study with cross sectional method. The population in this study was all mothers who had children with malnutrition status at Cebongan Community Health Center who were selected using total sampling technique, namely 27 people. The results showed that there was no relationship between malnutrition status of under-five children with maternal education (p=0.975), LBW (p=0.670) and exclusive breastfeeding (p=0.083) at Cebongan CHC Salatiga.